Hybrid Lattice-Boltzmann-Potential Flow Simulations of Turbulent Flow around Submerged Structures - Christopher M. O’Reilly; Stephan T. Grilli; Christian F. Janßen; Jason M. Dahl; Jeffrey C. Harris (Journal of Marine Science and Engineering, 2022)
We report on the development and validation of a 3D hybrid Lattice Boltzmann Model (LBM), with Large Eddy Simulation (LES), to simulate the interactions of incompressible turbulent flows with ocean structures. The LBM is based on a perturbation method, in which the velocity and pressure are expressed as the sum of an inviscid flow and a viscous perturbation. The far- to near-field flow is assumed to be inviscid and represented by potential flow theory, which can be efficiently modeled with a Boundary Element Method (BEM). The near-field perturbation flow around structures is modeled by the Navier–Stokes (NS) equations, based on a Lattice Boltzmann Method (LBM) with a Large Eddy Simulation (LES) of the turbulence. In the paper, we present the hybrid model formulation, in which a modified LBM collision operator is introduced to simulate the viscous perturbation flow, resulting in a novel perturbation LBM (pLBM) approach. The pLBM is then extended for the simulation of turbulence using the LES and a wall model to represent the viscous/turbulent sub-layer near solid boundaries. The hybrid model is first validated by simulating turbulent flows over a flat plate, for moderate to large Reynolds number values, Re ∈[3.7×104;1.2×106]; the plate friction coefficient and near-field turbulence properties computed with the model are found to agree well with both experiments and direct NS simulations. We then simulate the flow past a NACA-0012 foil using a regular LBM-LES and the new hybrid pLBM-LES models with the wall model, for Re = 1.44×106. A good agreement is found for the computed lift and drag forces, and pressure distribution on the foil, with experiments and results of other numerical methods. Results obtained with the pLBM model are either nearly identical or slightly improved, relative to those of the standard LBM, but are obtained in a significantly smaller computational domain and hence at a much reduced computational cost, thus demonstrating the benefits of the new hybrid approach.

The Quilt of Sustainable Ocean Governance: Patterns for Practitioners - Robert L. Stephenson; Alistair J. Hobday; Edward H. Allison; Derek Armitage; Kate Brooks; Alida Bundy; Christopher Cvitanovic; Mark Dickey-Collas; Natalia de Miranda Grilli; Catalina Gomez; Astrid Jarre; Laura Kaikkonen; et al. (Frontiers in Marine Science, 2021)
In recent decades, scientists and practitioners have increasingly focused on identifying and codifying the best ways to manage activities in marine systems, leading to the development and implementation of concepts such as the social-ecological systems approach, ecosystem-based management, integrated management, marine spatial planning, participatory co-management, and the precautionary approach. To date, these concepts appear as separate entities: they have parallel literature streams; have been applied most often individually in attempts to improve governance and management; and in many ways, seem to be competing for attention. This patchwork of approaches may be hindering effective ocean governance. We propose that desirable features from these frameworks could be woven together to form the basis of more effective and equitable ocean governance arrangements across contexts, sectors, and scales. This article synthesizes the efforts of an IMBeR (Integrated Marine Biosphere Research Project) conference session and working group, that brought together experts in these diverse concepts with the objective of producing a synthesis of how they could be more effectively integrated for improved ocean sustainability outcomes. We reviewed and compared the concepts in terms of (a) the need to achieve a comprehensive suite of sustainability objectives, (b) similarities and differences in their scope, and (c) their place in practical management, policy and regulation. Achieving greater cross-sectoral integration, or a more holistic perspective on management for sustainability is at the core of each concept. All deal with aspects of governance and most, with improved participation in governance. The major differences in the origin and historical application of each concept are reflected in the degree of implicit or explicit focus given to different objectives of sustainability. Overall, the concepts are especially strong for ecological and institutional or governance considerations, moderately strong for economic aspects, and weakest for the social-cultural pillar of full spectrum sustainability. There is no panacea, and no emergent hierarchy among concepts. Some concepts fit better with top-down legislation-based efforts, others with more bottom-up stakeholder driven efforts. The selection of the core concepts for a situation will depend in a large part on which concepts are specified, or demand focus, in the legal and policy context of the situation (or area) of interest. No matter how influential or dominant a single concept might be, pragmatically, different concepts will be used in different areas, and there may always be the need for a combination of concepts and objectives woven together to achieve a cohesive quilt of sustainability.

Modeling of SMF tsunami hazard along the upper US East Coast: detailed impact around Ocean City, MD - Stephan T. Grilli; Christopher O’Reilly; Jeffrey C. Harris; Tayebeh Tajalli Bakhsh; Babak Tehranirad; Saeideh Banihashemi; James T. Kirby; Christopher D. P. Baxter; Tamara Eggeling; Gangfeng Ma; Fengyan Shi (Natural Hazards, 2015)

Mechanisms related to the cardioprotective effects of protein kinase C epsilon (PKC ɛ) peptide activator or inhibitor in rat ischemia/reperfusion injury - Jane Chun-wen Teng; Helen Kay; Qian Chen; Jovan S. Adams; Christopher Grilli; Giuseppe Guglielmello; Christopher Zambrano; Samuel Krass; Adrian Bell; Lindon H. Young (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)